Assessment of postoperative pain with pre-incisional anesthetic infiltration in cholecystectomies (Revista Argentina de Cirugía, 2021)
Background: laparoscopic cholecystectomy is a frequent procedure with minor post-operative pain compared to open surgery, but still not accepted as an outpatient treatment.Objective: to demonstrate if infiltration with local anesthetics before incision would attenuate postoperative pain.Material and methods: two groups were settled, one received infiltration with local anesthetic (Ropivacaina) and the other one with saline solution. We included 140 patients, of which 62 were the experimental group and 75 the control group. Three were excluded for conversion to open surgery. Outcome measures: the pain was quantified at 3, 6, 12 and 24 postoperative hours by the use of numerical verbal graduation scale. A variance analysis for repeated measures (ANOVA) was carried outto compare the effect of the treatment.Results: patients treated with local anesthetics before incision showed a statistically significant di- fference (p < 0.001) regarding postoperative pain when compared to patients who received saline solution.Conclusions: having measured the pain on all individuals in four periods, we observed that the values of the anesthetic-treated group are lower than those of the placebo-treated group.
Keywords: laparoscopic cholecystectomy; postoperative pain; local anesthesia